Pengaruh Pencegahan Fraud Pengadaan Barang, Audit Internal dan Sistem Informasi Akuntansi Terhadap Efektivitas Persediaan Obat-Obatan di RSIA Santa Anna Bandar Lampung - Marta Mei Novalia Haloho; Darwin Warisi; Amelia Anwar (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the effect of fraud prevention in goods procurement, internal audit, and accounting information systems on the effectiveness of medicine supplies at RSIA Santa Anna Bandar Lampung. This research uses a quantitative descriptive approach where the data processing is carried out statistically. The data source used in this research is primary data obtained from distributing questionnaires to Finance and Pharmacy Installation employees at RSIA Santa Anna Bandar Lampung, then processed using the t-test method with the help of SPSS version 22. Based on the results of the coefficient of determination test, the effect of fraud prevention, Internal audit, and accounting information systems accounted for 75.9% of the effectiveness of medicine supplies at RSIA Santa Anna Bandar Lampung. It is necessary to improve internal audit and accounting information systems optimally to increase the effectiveness of medicine supplies at RSIA Santa Anna Bandar Lampung.